Characteristics of lymphoid cell effector cytotoxicity mechanisms in patients with sinonasal neoplasms - Nazaranka, Elizaveta; Morozova, Natallia; Vialichka, Alesia; Kolyadich, Zhanna; Nizheharodava, Darya (Journal of the Belarusian State University. Ecology, 2024)
The immune response to tumors is primarily mediated through effector cytotoxic reactions, which enable the direct removal of transformed cells in the body. Granule-mediated cytotoxicity is one of the main protective antitumor mechanism, which includes the release of lytic proteins into the immunological synapse between the effector cell and the target. Studying the features of this cytotoxic mechanism is promising for identifying molecular biomarkers that can help track the progression of tumor malignancy and develop new approaches to targeted immunotherapy. This article presents the results of LAMP-1/CD107a expression and intracellular granzyme B production by cytotoxic lymphoid cells in co-cultures with tumor cell line K562 from patients with benign and malignant sinonasal tumors, who were treated in the department of head and neck tumors of the Republican Scientific and Practical Center of Oncology and Medical Radiology named after N.N. Alexandrov in 2023-2024. The comparison group consisted of patients with polypous rhinosinusitis, the control group was represented by healthy individuals. The expression of the markers was determined by flow cytofluorometry. The study revealed an increase in the number of NK cells and a decrease in the number of T cells in cultures in patients with benign and malignant sinonasal neoplasms compared with the control group. An increase in the CD107a expression and intracellular granzyme B production by T cells from patients with malignant sinonasal neoplasms in co-cultures with K562 as compared with the control group was established, that correlates with the degree of disease malignancy (R=0.48, p=0.009 for T-cells expressing CD107, and R=0.40, p=0.03 for cells producing granzyme B). At the same time, the CD107a expression and the granzyme B production by NK-cells in co-cultures with K562 was significantly reduced in patients with both benign and malignant neoplasms. The obtained data indicates that effector T cells in patients with malignant sinonasal neoplasms are involved in the antitumor response, predominantly using the mechanism of granule-mediated cytotoxicity, allowing to consider subpopulations of CD107a- and granzyme B-positive T cells as potential prognostic markers of malignancy of the tumor process.